2013
DOI: 10.5713/ajas.2012.12430
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Alpha Lipoic Acid Improves Body Composition, Meat Quality and Decreases Collagen Content in Muscle of Broiler Chickens

Abstract: A total of 192 broiler chicks were used to evaluate the influence of dietary α-lipoic acid (ALA) on growth performance, carcass characteristics and meat quality of broiler chickens with the purpose of developing a strategy to prevent the occurrence of pale, soft, and exudative (PSE) meat and to improve the meat quality of broilers. At 22 d of age, birds were allocated to 4 ALA treatments (0, 400, 800, and 1200 ppm). The results showed that dietary ALA significantly decreased average feed intake (AFI), average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 43 publications
(61 reference statements)
2
24
0
2
Order By: Relevance
“…Another study reported of feed fortification of birds with lipoic acid at the rate of 900 mg/kg can influence growth performance. They reported that higher dose of ALA inhibited growth performance of birds resulting in lower weight gain and higher feed conversion efficacy making it economically unfeasible approach (El‐Senousey, Fouad, Yao, Zhang, & Shen, ). Furthermore, they also reported that 500 mg/kg lipoic acid supplementation improved growth and increased antioxidant ability of resulting meat.…”
Section: Growth Performance Measurementsmentioning
confidence: 99%
“…Another study reported of feed fortification of birds with lipoic acid at the rate of 900 mg/kg can influence growth performance. They reported that higher dose of ALA inhibited growth performance of birds resulting in lower weight gain and higher feed conversion efficacy making it economically unfeasible approach (El‐Senousey, Fouad, Yao, Zhang, & Shen, ). Furthermore, they also reported that 500 mg/kg lipoic acid supplementation improved growth and increased antioxidant ability of resulting meat.…”
Section: Growth Performance Measurementsmentioning
confidence: 99%
“…Bai et al (2012) determined that ALA supplementation to the diet of sows during late-gestation and lactation improved the activity of antioxidant enzymes in the serum and improved the performance of sows and their nursing piglets. In broiler chickens, dietary ALA inhibited body fat deposition, decreased muscle glycolysis at early postmortem, and improved the water holding capacity, indicating that ALA supplementation could prevent the occurrence of PSE (pale, soft, exudative) meat (El-Senousey et al, 2013). Lipid peroxidation level, superoxide dismutase, and catalase enzyme activities and glutathione amounts in Japanese quail under heat stress conditions were ameliorated with the addition of ALA to the diet (Halıcı et al, 2012).…”
Section: Introductionmentioning
confidence: 96%
“…However, several publications have reported conflicting findings. For example, one reported negative growth performance in ALA-fed broilers ( EI-Senousey et al, 2013 ), while another study reported ALA had no effect on growth performance in broilers ( Hamano et al, 1999 ). Moreover, Kim et al (2011) demonstrated that 0.5% ALA administration decreases serum TG significantly in rats.…”
Section: Introductionmentioning
confidence: 99%